The young vegetarian's companion - Parr, Jan.; Durham, Sarah (New York : Franklin Watts, 1996)
Discusses the ethical, religious, health, environmental, and personal reasons for being a vegetarian and some of the lifestyle issues involved in this choice.
Includes bibliographical references (p. 137-138) and index.
Wilson's Senior High School.
Young Adult
Keywords: Vegetarianism -- Juvenile literature; Vegetarianism; Vegetarianism